ANALISIS PELAKSANAAN KEBIJAKAN SATUAN TUGAS PENANGANAN COVID-19 MENGENAI PENERBITAN SURAT EDARAN (SE) NOMOR 11 TAHUN 2022 TENTANG KETENTUAN PERJALANAN ORANG DALAM NEGERI PADA MASA PANDEMI CORONAVIRUS DISEASE 2019 (COVID-19) - Gunawan Widjaja; Retnaningtyas Insyira, Anggia Az Zahra, Nadila Citra Aprilia, Chairunnissa, Muhammad Rayyan Firdaus, (INTELIGENSIA MEDIA, 2022)
Covid-19, since it was first discovered in 2019, is considered a very dangerous infectious disease. So much so that almost all countries had banned travel. In 2022, the Covid-19 Handling Task Force led by the Head of the NATIONAL DISASTER MANAGEMENT AGENCY (BNPB) issued Circular Letter (SE) No. 11 of 2022 regarding Travel Provisions for Domestic People during the Covid- 19 Pandemic. This research was conducted to examine the implementation of the policies outlined in the SE. This research is empirical by taking a sample of 50 people who, after the issuance of the SE, traveled domestically. A list of questions was created and submitted in the form of a google-form, to be filled in by volunteers who had traveled domestically after the issuance of the SE. The results of the research and analysis showed that the people who were asked for their opinions showed compliance with the SE and did not cause Covid-19 transmission.